The Impact of Profit and Cash Flow on Financial Distress Conditions in Hotel, Restaurant, and Tourism Sub-Sector Companies Listed on The Indonesia Stock Exchange - Umar Hamdan Nasution (LPPM Universitas BSI, 2023)
This study aims to ascertain the effect that applying job expansion has on employee engagement. Purposive sampling was employed in the research at PT. Bank Aceh Syariah Medan Region, resulting in a sample size of 346 respondents. Multiple linear regression analysis is the method utilized for analysis. The findings indicated that employee engagement was impacted by employment expansion. The results of the t-test, which had a significance level of 0.000 but a lower threshold of 0.05 (0.000<0.05), clearly demonstrated this. Additionally, the results of the test for the coefficient of determination reveal that an increase in employee engagement has a 28% positive impact on job size, with the remaining 72% being influenced by other factors. A tough work expanding inspires sentiments of significance. High engagement results from self-meaning that develops as a result of task design that is in line with objectives and self-values. Additionally, work arrangements that encourage employees to create meaning in their work result in higher levels of engagement than those that downplay the significance of meaningful work in employees' lives.